1992
DOI: 10.1093/infdis/166.3.531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virus Load in the Pathogenesis of Lentivirus-Induced Lymphoid Interstitial Pneumonia

Abstract: To better define the relationship between ovine lentivirus (OvLV) infection and respiratory disease, pulmonary leukocytes and postmortem lung specimens from 42 sheep seropositive or at risk for OvLV infection were obtained. The lungs were examined for lesions of lymphoid interstitial pneumonia (LIP), and animals were categorized into five groups by severity of LIP and OvLV serologic status. The presence of OvLV in alveolar macrophages was established by proviral DNA amplification using the polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1
4

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 48 publications
1
36
1
4
Order By: Relevance
“…Links have been made between the presence of provirus in the lung of naturally OPPV-infected sheep or the amount of provirus in tissues and peripheral blood mononuclear cells of experimentally CAEV-infected goats and the degree of histological lesions in tissues. 7,13,48 Furthermore, a statistically significant correlation was observed between the amount of provirus in lung alveolar macrophages and adherent peripheral blood mononuclear cells of naturally infected sheep and the degree of histological lung lesions. 55 More recently, we showed that peripheral blood leukocyte ovine progressive pneumonia provirus levels correlate significantly with histological lesion scores in any of the affected tissues.…”
Section: Discussionmentioning
confidence: 83%
“…Links have been made between the presence of provirus in the lung of naturally OPPV-infected sheep or the amount of provirus in tissues and peripheral blood mononuclear cells of experimentally CAEV-infected goats and the degree of histological lesions in tissues. 7,13,48 Furthermore, a statistically significant correlation was observed between the amount of provirus in lung alveolar macrophages and adherent peripheral blood mononuclear cells of naturally infected sheep and the degree of histological lung lesions. 55 More recently, we showed that peripheral blood leukocyte ovine progressive pneumonia provirus levels correlate significantly with histological lesion scores in any of the affected tissues.…”
Section: Discussionmentioning
confidence: 83%
“…Subsequent reanalysis of the data from an earlier pathogenesis study showed that the presence of lung lesions (mild, moderate, or severe) correlates significantly with the presence of provirus in alveolar macrophages using PCR specific for ltr and pol (Fisher's exact test, two-sided P value ϭ 0.0003) (4). In addition, sheep with lung lesions had Ͼ10-fold more pol copies in their alveolar macrophages, determined by a quantitative PCR (qPCR), than sheep without lung lesions (27).…”
mentioning
confidence: 99%
“…OPPV provirus is found in cells of the macrophage and monocyte lineage without causing cellular ablation (13,14). Specifically, OPPV provirus has been detected in many cell types, including lung type I and II pneumocytes, interstitial and alveolar macrophages, endothelial cells, fibroblasts, colostrum cells, cumulus cells, peripheral blood mononuclear cells, and peripheral blood leukocytes (PBL) (2,4,6,8,11,17,18,27). Plasma viremias are thought to be low in OPPV-infected sheep (3); therefore, measuring OPPV provirus loads may be the best way to quantitate virus in vivo.…”
mentioning
confidence: 99%
“…Other organ-specific changes, such as smooth muscle hyperplasia in the lung or demyelination in the central nervous system, also occur (6). Virus is usually cell associated, with only low frequencies of infected cells being detected even in lesions that are well developed (8,35,47). How the virus persists has been under investigation for many years with both latent or restricted infection and infection of myeloid precursors put forward as strategies which may aid the virus to survive in the host (19,20,44).…”
mentioning
confidence: 99%